ASSESSMENT OF ANTIOXIDANT ACTIVITY OF SOME OROBANCHACEAE SPECIES FROM ARMENIA (Proceedings of the YSU B: Chemical and Biological Sciences, 2022)
Holoparasitic plants of the family Orobanchaceae are represented by 36 species belonging to 4 genera in Armenia. Despite the fact that the secondary metabolites and their pharmacological properties are not well studied, the limited data on this topic is already a promising source for different bioactive compounds. In this paper, we are representing the antioxidant properties and phenolic content of four species belonging to Orobanchaceae family. The highest antioxidant activities were recorded for Orobanche kurdica alcoholic extract. Water soluble phenols may explain the great antioxidant capacity of the aqueous extract of Diphelypaea tournefortii.
Keywords: Orobanchaceae; parasitic plants; antioxidant activity; phenols